Curcumin-loaded nanoparticles ameliorate glial activation and improve myelin repair in lyolecithin-induced focal demyelination model of rat corpus callosum. (1st May 2018) - Naeimi, Reza; Safarpour, Fatemeh; Hashemian, Mona; Tashakorian, Hamed; Ahmadian, Seyed Raheleh; Ashrafpour, Manouchehr; Ghasemi-Kasman, Maryam
Graphical abstract: Highlights: CS-ALG-STPP NPs enhance the bioavailability of curcumin. Curcumin-loaded NPs reduce demyelination level of corpus callosum. Curcumin-loaded NPs ameliorate glial activation in LPC-induced demyelination model. Abstract: Curcumin has been introduced as effective anti-inflammatory agent in treatment of several inflammatory disorders. Despite the wide range pharmacological activities, clinical application of curcumin is restricted mainly due to the low water solubility of this substance. More recently, we could remarkably improve the aqueous solubility of curcumin by its encapsulation in chitosan-alginate-sodium tripolyphosphate nanoparticles (CS-ALG-STPP NPs). In this study, the anti-inflammatory and myelin protective effects of curcumin-loaded NPs were evaluated in lysolecithin (LPC)-induced focal demyelination model. Pharmacokinetic of curcumin was assessed using high performance liquid chromatography (HPLC). Local demyelination was induced by injection of LPC into corpus callosum of rats. Animals were pre-treated with intraperitoneal (i.p.) injections of curcumin or curcumin-loaded NPs at dose of 12.5 mg/kg, 10 days prior to LPC injection and the injections were continued for 7 or 14 days post lesion. Hematoxylin and eosin (H&E) staining and immunostaining against activated glial cells including astrocytes and microglia were carried out for assessment of inflammation level in lesion site. Myelin specific staining was performed to evaluate the effect of curcumin-loaded NPs on myelination of LPC receiving animals. HPLC results showed the higher plasma concentration of curcumin after administration of NPs. Histological evaluation demonstrated that, the extent of demyelination areas was reduced in animals under treatment of curcumin-loaded NPs. Furthermore, treatment with curcumin-loaded NPs effectively attenuated glial activation and inflammation in LPC-induced demyelination model compared to curcumin receiving animals. Overall; these findings indicate that treatment with curcumin-loaded NPs preserve myelinated axons through amelioration of glial activation and inflammation in demyelination context.